Ali je vegansko prehranjevanje primerno za športnike in nosečnice? - Jakše, Boštjan (Šport (Ljubljana), 2017)
For more than half a century, the scientific researches have been consistently demonstrating that a vegan diet is associated with a lower risk for common chronic diseases and a longer life expectancy. Due to preventive protection of a well-planned vegan diet and due to the benefits this diet can provide for an efficient training, recovery after it, and a stronger immune system, there is a growing number of athletes who decide on a vegan diet. The British Dietetic Association (BDA) and the Academy of Nutrition and Dietetics (AND) state that appropriately planned vegetarian, including vegan, diets are healthful and nutritionally adequate and appropriate for all stages of the life cycle, including pregnancy, lactation, infancy, childhood, adolescence and older adulthood. AND indicates that a vegan diet is also appropriate for the needs of an athlete. The purpose of the article is to justify the adequacy of a vegan diet for the needs of an athlete and during the period of pregnancy with a relative scientific transparency.
Keywords: athlete; chronic diseases; kronične bolezni; nosečnost; pregnancy; prehranjevanje; športnik; training; trening; vegan diet; vegani; vegansko prehranjevanje